PERANCANGAN SISTEM INFORMASI KEUANGAN SEKOLAH BERBASIS WEB MENGGUNAKAN METODE PROTOTYPING (STUDI KASUS : SMA NEGERI 1 KADUGEDE KABUPATEN KUNINGAN) - Mas’al Mas’al; Muhammad Hatta; Lena Magdalena (Jurnal Digit, 2018)
Abstract Financial management in schools is a very important part for any activity that is in school would have financial need for the smooth operation of the school. At the High School ( SMA ) 1 Kadugede one of the problems that occur are recording errors in the data management process especially the financial part that has not been computerized since still using conventional recording, that the officer was recorded every student payment recapitulation into a ledger or cash book. This research aims to design and build the Financial Management Information Systems in the High School ( SMA ) 1 Kadugede to be more flexible and dynamic as well as minimize the errors in inputting data and optimize storage and data security. Resulting in Financial Management Information Systems School of well-organized and helped finance officers in the processing of financial data. This study will also outline the products produced at each stage of the analysis. Financial Management Information System School conducted a complete and detailed. The author of the research methods to solve a variety of problems that occur are observation, interviews, documentation, literature, system analysis, system design, testing, and implementation of the system, in order to produce a better change in the existing system. We hope this research can assist and facilitate the user in the process of processing the financial management of school finances in order can be processed effectively and efficiently. So that financial data can be realized with both and can generate accurate calculations. Keywords: Information, Systems, Financial, Management, School